Ultrasound-Assisted Enzymatic Extraction and Bioactivity Analysis of Polypeptides from Cordyceps militaris. (10th January 2023) - Xu, Lina; Guo, Shang; Li, Yanting; Guo, Weiwei; Guo, Xiaofei; Hong, Shasha
Abstract : Cordyceps militaris is rich in protein, polysaccharide, cordycepin, and other active components, with anticancer and antioxidation functions. In order to improve the economic value of C. militaris, the protein was extracted from its fruiting body by alkali-soluble acid precipitation process, and the extraction technology was optimized by orthogonal test. The polypeptide was obtained by digesting those proteins with a complex enzyme. And the antimicrobial and anticancer activities of those polypeptides were evaluated by measuring inhibitory zone and cytotoxicity. The results showed that the optimal extraction conditions of protein were as follows: pH of 8.5, material-to-water ratio of 1 : 28, extraction time of 3.5 h, extraction three times, and the highest protein yield was 45.06%. The optimum enzymatic hydrolysis process of C. militaris polypeptide solution was as follows: the ratio of alkaline protease to papain was 4 : 3, the optimum temperature was 55°C, pH was 7.2, the enzyme dosage was 7000 U/mL, the enzymolysis time was 3.5 h, and the highest yield of peptide was 16.73%. Under those conditions, the polypeptides prepared from C. militaris (<3000 Da) showed good antibacterial activity against Escherichia coli, Bacillus subtilis, and Staphylococcus aureus, with inhibitory zones of (12.08 ± 0.22), (6.67 ± 0.12), and (10.32 ± 0.23) mm, respectively. The results showed that the SAO-S (IC50 = 0.49 mg/L) and T24 (IC50 = 0.23 mg/L) were significantly inhibited by C. militaris polypeptide. Results from this study suggest that polypeptides can be utilized as a new approach for bioactive compounds production from C. militaris .